STRATEGI PENGEMBANGAN USAHA UNTUK MENINGKATKAN PENDAPATAN BUMDES KAMPUNG MARBIN KABUPATEN MAPPI: PENDEKATAN RISIKO BERBASIS ISO-31000 - Patabang, Ros; Sintha, Lis; Tewu, Denny; Hanafi, Agustina (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes factors influencing the income of BUMDes in Marbin Village, Mappi Regency, and formulates a risk-based development strategy for remote rural contexts. A qualitative method was employed through interviews with eight key informants and document analysis. Strategic analysis used the Ansoff framework and ISO 31000 for risk identification. Income is influenced by managerial, operational, market, and financial aspects, with key barriers being limited human resources and weak financial management. A focus strategy emphasizing cost efficiency, capacity building, and structured risk management is proposed to enhance income stability and business sustainability of the BUMDes.